Effects of swimming training at the intensity equivalent to aerobic/anaerobic metabolic transition in alloxan diabetic rats - de Oliveira, Camila A. M.; Luciano, Eliete; Marcondes, Maria Cristina C. G.; de Mello, Maria Alice R. (Elsevier B.V., 2007)
The present study was designed to determine the exercise intensity equivalent to the metabolic aerobic/anaerobic transition of alloxan diabetic rats, through lactate minimum test (LMT), and to evaluate the effects of swimming exercise at this intensity (LM) on the glucose and protein metabolism of these animals. Adult male Wistar rats received alloxan (SD, alloxan-injected rats that remained sedentary) intravenously (30 mg kg(-1) body weight) for diabetes induction. As controls (SC, vehicle-injected rats that remained sedentary), vehicle-injected rats were utilized. Two weeks later, the animals were submitted to oral glucose tolerance test (oGTT) and LMT. After the tests, some of the animals were submitted to swimming exercise training [TC (vehicle-injected rats that performed a 6-week exercise program) and TD (alloxan-injected rats that performed a 6-week exercise program)] for I h day(-1), 5 days week(-1), with an overload equivalent to LM determined by LMT, for 6 weeks. At the end of the experiment, the animals were submitted to a second LMT and oGTT, and blood and skeletal muscle assessments (protein synthesis and degradation in the isolated soleus muscle) were made. The overload equivalent to LM at the beginning of the experiment was lower in the SID group than in the SC group. After training, the overload equivalent to LM was higher in the TC and TD groups than in the SC and SD groups. The blood glucose of TD rats during oGTT was lower than that of SD rats. Protein degradation was higher in the SD group than in other groups. We conclude that LMT was sensitive to metabolic and physiologic alterations caused by uncontrolled diabetes. Training at LM intensity improved aerobic condition and the glucose and protein metabolism of alloxan diabetic rats. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: alloxan; aerobic/anaerobic transition; diabetes; lactate minimum test; rats; swimming exercise